(untitled) (Journal of Human Sciences, 2023)
Hearing disability is considered one of the disabilities that most affect a person, as it represents an obstacle to communication and academic excellence, and it also greatly affects the individual’s psyche and social relations, which prompted researchers to conduct this study, to learn more about the most important problems that the deaf and hard of hearing suffer from. all levels. Through the opinions of a number of students of the Department of Hearing and Speech at the College of Medical Technology, Surman, which numbered (50) hearing and speech specialist, using the analytical descriptive approach and the questionnaire as a tool. To collect data and information, and by using a number of statistical methods represented by the arithmetic mean, standard deviation, percentage, and relative weight, as the results indicated that there was a high agreement among the sample on the existence of academic, social, psychological, behavioral and medical problems at a large to very large rate. Thus, we recommend the need to educate the parents of these children in particular, and society in general, about the concept of hearing disability and the resulting problems that hinder the affected child from living normally, which negatively affects his life in general.